2006
DOI: 10.1002/bit.21061
|View full text |Cite
|
Sign up to set email alerts
|

Automated maintenance of embryonic stem cell cultures

Abstract: Embryonic stem cell (ESC) technology provides attractive perspectives for generating unlimited numbers of somatic cells for disease modeling and compound screening. A key prerequisite for these industrial applications are standardized and automated systems suitable for stem cell processing. Here we demonstrate that mouse and human ESC propagated by automated culture maintain their mean specific growth rates, their capacity for multigermlayer differentiation, and the expression of the pluripotency-associated ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(69 citation statements)
references
References 16 publications
0
68
0
1
Order By: Relevance
“…Barrier isolators and cGMP conditions have been adapted for pharmaceutical and biotechnological processing avoiding crosscontamination and operator exposure [26]. A number of studies have previously demonstrated that commercially available automation platforms can be used to develop robust stem cell production processes based on two dimensional cell culture systems [12,[23][24][25][26][27][28]. Automated platforms enable accurate and repeatable control of plate handling and liquid handling velocities and forces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barrier isolators and cGMP conditions have been adapted for pharmaceutical and biotechnological processing avoiding crosscontamination and operator exposure [26]. A number of studies have previously demonstrated that commercially available automation platforms can be used to develop robust stem cell production processes based on two dimensional cell culture systems [12,[23][24][25][26][27][28]. Automated platforms enable accurate and repeatable control of plate handling and liquid handling velocities and forces.…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports have used commercially available automation platforms for the maintenance of stem cells under 2D culture conditions [12,[23][24][25][26][27][28]. By eliminating reliance upon highly skilled operators these systems can enhance the reproducibility of stem cell bioprocesses.…”
Section: Introductionmentioning
confidence: 99%
“…Cela implique d'éviter les systèmes de coculture, de travailler en milieu défini et avec des techniques de dissociation adaptées, tout en veillant à ne pas induire d'instabilité génétique [28]. Ces mêmes protocoles devront être compatibles avec un changement d'échelle, ce qui nécessite une automatisation des processus par des plates-formes robotiques [29] ou le recours à des bioréacteurs [30,31] (➜). Les protocoles de différenciation devront également être optimisés, de manière à tendre vers une population pure, homogène et la plus mature possible, les populations intermé-diaires et terminales devant être caractérisées de manière approfondie.…”
Section: Innovations Technologiques Indispensables Pour L'utilisationunclassified
“…6 In these fields, the maintenance of homogeneous cell populations and the reproducible control of differentiation are important issues, because behavior of hiPS cells is severely affected by the surrounding microenvironment, which includes the size and shape of the cellular aggregates during passage and differentiation, the geometrical arrangement of the adhered cellular aggregates (i.e., colonies), the timing of medium change as well as addition of differentiation factors, and composition of the extracellular matrix. 7,8 The development of processes, ideally involving programmed perfusion [9][10][11] and automated cultivation, [12][13][14] to control the culture microenvironment would overcome these problems and allow this approach to be applied to industrial applications.…”
Section: Introductionmentioning
confidence: 99%